Effectiveness of Puppet-Assisted Media in Strengthening Religious Characteristic Value and Language Skill of Early Childhood - Musyawaroh, Musyawaroh; Sutarto, Joko; Aeni, Kurotul (Universitas Negeri Semarang, 2021)
The growth and development of early childhood should be stimulated by strengthening the religious character value and the language skill; therefore, children have noble behavior. This research aimed to develop the religious behavior attitude and the language skill of early childhood. The research object was hand-puppet-assisted media to strengthen the religious character value and the language skill. The population in this research were 30 children aged 5-6 years of the group B at TK ABA 04 Penaruban of the experiment class, and 30 children of the group B at TK ABA 03 Bumiayu of the control class. The data collection techniques used observation sheets, interviews, and documentation. The analysis used was the t-test using SPSS for windows version 16.00. The data analysis used the hand-puppet-assisted storytelling method. The hypothesis test results showed that the average pretest value of the experiment class was 18.21, and the average posttest was 21.00, so that it increased by 2.79. It was also found that the tcount> ttable at a significant level of 5% (15.649 > 2.037) and with a p-value of < 0.05, which means that it can be concluded that there was a significant increase in the score of student learning outcomes of the experiment group. Thus, it can be concluded that the strengthening of the religious character valueand the language skill of children aged 5-6 years at TK ABA 04 Penaruban using the hand-puppet-assisted storytelling method was more effective than using conventional media.